2018
DOI: 10.1084/jem.20180776
|View full text |Cite
|
Sign up to set email alerts
|

Lupus antibodies induce behavioral changes mediated by microglia and blocked by ACE inhibitors

Abstract: Cognitive impairment occurs in 40-90% of patients with systemic lupus erythematosus (SLE), which is characterized by autoantibodies to nuclear antigens, especially DNA. We discovered that a subset of anti-DNA antibodies, termed DNRAbs, cross reacts with the N-methyl-d-aspartate receptor (NMDAR) and enhances NMDAR signaling. In patients, DNRAb presence associates with spatial memory impairment. In a mouse model, DNRAb-mediated brain pathology proceeds through an acute phase of excitotoxic neuron loss, followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
179
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 125 publications
(189 citation statements)
references
References 59 publications
10
179
0
Order By: Relevance
“…In DNRAb + mice, an NMDAR–high mobility group box chromosomal protein 1–C1q complex forms at synapses on neuronal dendrites, targeting them for destruction. C1q knockout DNRAb + mice maintain normal dendritic complexity and spine density following LPS administration , confirming a critical contribution of C1q in DNRAb‐mediated pathology.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…In DNRAb + mice, an NMDAR–high mobility group box chromosomal protein 1–C1q complex forms at synapses on neuronal dendrites, targeting them for destruction. C1q knockout DNRAb + mice maintain normal dendritic complexity and spine density following LPS administration , confirming a critical contribution of C1q in DNRAb‐mediated pathology.…”
Section: Introductionmentioning
confidence: 68%
“…We have shown that angiotensin-converting enzyme (ACE) inhibitors, through their centrally acting effects, reduce microglial activation, prevent loss of dendritic arborization, and prevent spatial memory impairment in DNRAb+ mice (42). Treatment with captopril after onset of microglial activation also restored dendritic arborization and spine density (Figure 3), suggesting that surviving neurons in this model do not experience irreversible damage.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Of note, these functional properties are similar to those recently identified in IFN‐α‐treated microglia (Li et al, ). It has also recently been demonstrated that microglia mediate pathologic dendritic pruning of hippocampal neurons in an anti‐DNA antibody‐mediated mouse model of CNS lupus (Nestor et al, ). Together, these findings link the response of microglia to IFN‐I to the pathogenesis of CNS lupus in mouse models and may also contribute to disease in patients with CNS lupus.…”
Section: The Response Of Microglia In Il‐6‐ and Ifn‐i‐mediated Neuroimentioning
confidence: 99%
“…LPS-treated mice immunogenized to generate DNRAbs and patient-derived DNRAbs display a gamut of pathologies in the hippocampus: aberrant excitatory signaling, apoptosis, dendritic pruning, and microglial activation 10,11,19 . These mice also display expanded place fields in the hippocampus and defects in spatial memory 2,19 . These studies are essential to defining the pathology of the neuropsychiatric component of SLE, but do not define the specific NMDARs that mediate these effects.…”
Section: Introductionmentioning
confidence: 99%